2002
DOI: 10.1101/lm.47802
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Olfactory Memory Circuits: Region-Specific c-fos Activation After Odor-Reward Associative Learning or After Its Retrieval

Abstract: Although there is growing knowledge about intracellular mechanisms underlying neuronal plasticity and memory consolidation and reconsolidation after retrieval, information concerning the interaction among brain areas during formation and retrieval of memory is relatively sparse and fragmented. Addressing this question requires simultaneous monitoring of activity in multiple brain regions during learning, the post-acquisition consolidation period, and retrieval and subsequent reconsolidation. Immunoreaction to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
101
1
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 23 publications
(26 reference statements)
9
101
1
1
Order By: Relevance
“…This could be because of the relative facility with which the task is learned. Rats rarely make a choice error after the first two trials, although their performance further improves in terms of latency (Tronel and Sara, 2002). Only a few human studies have reported a correlation between the actual spindle density and acquisition rate or spindle density and retention (Clemens et al, 2005), whereas others relate spindle density merely to the subject's cognitive abilities regardless of whether learning occurred before sleep (Schabus et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be because of the relative facility with which the task is learned. Rats rarely make a choice error after the first two trials, although their performance further improves in terms of latency (Tronel and Sara, 2002). Only a few human studies have reported a correlation between the actual spindle density and acquisition rate or spindle density and retention (Clemens et al, 2005), whereas others relate spindle density merely to the subject's cognitive abilities regardless of whether learning occurred before sleep (Schabus et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Then a baseline activity was recorded for Ն3 h. In experiment 1, on the day after the baseline recording, an animal was trained either on the three-way odor-reward association "nose-poke" task (n ϭ 9) or fourway odor-reward association "digging" task (n ϭ 16). The nose-poke task has been used in our laboratory for rapid appetitive learning in rats and was described in detail previously (Tronel and Sara, 2002). Briefly, three sponges with a hole in the middle and impregnated with different odors were placed in the corners of the experimental box (1 ϫ 1 ϫ 1 m).…”
Section: Methodsmentioning
confidence: 99%
“…A previous experiment has found that lesions of the surrounding areas damaged in the representative lesions have a mild effect on working memory but do not impair reward learning (Mitchell & Dalrymple-Alford, 2005), so they probably did not affect the devaluation results. There is a small amount of evidence linking lateral habenula to reward processes (Matsumoto & Hikosaka, 2006;Tronel & Sara, 2002 does not appear to be interconnected with any of the areas involved in devaluation other than MD (Sutherland, 1982), such as BLA, OFC, PLC or DMS (Felton, Linton, Rosenblatt, & Morell, 1999;Klemm, 2004;Sutherland, 1982), so damage to lateral habenula probably did not affect the results.The role of non-MD damage in the deficits was examined in several ways. First, analyses of experiments that demonstrated lesion effects found no effect of the amount of damage to the lateral habenula, hippocampus or thalamus beyond MD.…”
mentioning
confidence: 99%
“…In contrast to adult odor-LiCl learning, which relies on the amygdala (Touzani and Sclafani 2005), this early-life, odoraversion learning relies on the olfactory bulb until the pup approaches weaning age, when the amygdala is incorporated into the learning circuitry (Shionoya et al 2006). In contrast, if infant rats receive an odor paired with a moderately painful stimulus (0.5-mA foot or tail shock, or tail pinch) the amygdala appears to be incorporated into this learning circuitry around postnatal day Here we expand assessment of the developing pups' odoraversion learning circuit by including the anterior and posterior piriform cortex, which have previously been demonstrated to be important for both pup and adult odor learning (Litaudon et al 1997;Barkai and Saar 2001;Mouly et al 2001;Mouly and Gervais 2002;Tronel and Sara 2002;Moriceau and Sullivan 2004;Sevelinges et al 2004;Wilson et al 2004;Roth et al 2006). We also extend the assessment of the development of odor-aversion learning by directly comparing a range of odor-aversion learning paradigms and including different intensities of shock.…”
mentioning
confidence: 99%
“…Here we expand assessment of the developing pups' odoraversion learning circuit by including the anterior and posterior piriform cortex, which have previously been demonstrated to be important for both pup and adult odor learning (Litaudon et al 1997;Barkai and Saar 2001;Mouly et al 2001;Mouly and Gervais 2002;Tronel and Sara 2002;Moriceau and Sullivan 2004;Sevelinges et al 2004;Wilson et al 2004;Roth et al 2006). We also extend the assessment of the development of odor-aversion learning by directly comparing a range of odor-aversion learning paradigms and including different intensities of shock.…”
mentioning
confidence: 99%